2008
DOI: 10.22358/jafs/66473/2008
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effects of different dietary levels of cellulose and fructooligosaccharides on fermentative processes in the caecum of rats

Abstract: Forty eight male Wistar rats were divided into 6 groups and fed over 4 weeks with diets containing 2.5, 5 or 10% addition of potentially inert carbohydrate cellulose (CEL) or easily fermentable fructooligosaccharides (FOS). In rats fed on CEL diets no substantial changes in the pH, caecal mass, as well as protein, ammonia and short-chain fatty acids (SCFA) concentration in the caecal digesta were observed; almost all microbial enzymes activity also was not modifi ed, except the activity of β-glucuronidase whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
22
1
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 23 publications
6
22
1
1
Order By: Relevance
“…The results of our experiment showing that neither cellulose (CEL) nor inulin (I) supplementation significantly affected final body weight of rats are in agreement with the observations reported in the earlier study, where diets were supplemented with 2.5, 5 and 10% of cellulose or fructooligosaccharides (FOS) (Jurgoński et al, 2008). …”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The results of our experiment showing that neither cellulose (CEL) nor inulin (I) supplementation significantly affected final body weight of rats are in agreement with the observations reported in the earlier study, where diets were supplemented with 2.5, 5 and 10% of cellulose or fructooligosaccharides (FOS) (Jurgoński et al, 2008). …”
Section: Discussionsupporting
confidence: 93%
“…Addition of cellulose did not influence total SCFAs pool. The latter observation is in agreement with results demonstrating that CEL affects caecal fermentative processes only to small extent; they suggested that CEL-diet can be applied as a suitable negative control while studying the properties of potentially prebiotic carbohydrates (Jurgoński et al, 2008).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Penurunan tebal lemak punggung dengan peningkatan sekam padi dalam ransum terjadi karena sekam padi mampu mengikat lemak ransum untuk diekskresikan bersama dengan feses. Hal ini sesuai dengan pendapat Jurkonski et al (2008) yang menyatakan bahwa partikel serat umumnya memiliki gugus penukar ion kation yang memiliki kemampuan seperti matriks spons untuk mengikat partikel lemak dengan ikatan intraluminal. Hasil ini sesuai dengan yang pernah dilaporkan oleh Wilfart et al (2007), bahwa peningkatan konsentrasi serat dalam ransum menyebabkan peningkatan kandungan ekstrak ether feses ternak babi.…”
Section: Karkas Ternak Babiunclassified